The Feeding Behavior and Dissatisfaction With Body Image of Female Basketball Athletes' A City Central São Paulo (Revista Brasileira Multidisciplinar, 2010)
The most important eating disorders are anorexia and bulimia nervosa. This study intended to appraise athletes' behavior related to food , weight control and body image. The obtained results were: 25% present light distortions of their body image and 16,66% show moderate distortions. Based on the silhouettes of Stunkard et al., 66,66% overestimate their weight, 16,66% show dissatisfaction in relation to their thinness, 16,67% are pleased with their body weight. The majority of the athletes presents proper body composition, but presents a distortion of their body image.
Keywords: Eating disorders; Basketball players; Body image.